Genetic Comparison of Oncomelania hupensis quadrasi (Möllendorf, 1895) (Gastropoda: Pomatiopsidae), the Intermediate Host of Schistosoma japonicum in the Philippines, Based on 16S Ribosomal RNA Sequence - Chua, James Christopher C.; Tabios, Ian Kim B.; Tamayo, Pebbles Grayle P.; Leonardo, Lydia R.; Fontanilla, Ian Kendrich C.; Fornillos, Raffy Jay C.; De Chavez, Emmanuel Ryan C.; Agatsuma, Takeshi; Kikuchi, Mihoko; Kato-Hayashi, Naoko; Chigusa, Yuichi (Science Diliman: A Journal of Pure and Applied Sciences; Vol 29 No 2 (2017), 2017)
Schistosomiasis japonica is a water-borne trematode infection transmitted by different subspecies of Oncomelania hupensis . As parasites may either co-evolve or locally adapt with their hosts, snail diversity, as revealed by morphometric and genetic studies, may reflect parasite diversity and elucidate snail susceptibility and transmission patterns. This study aimed to compare isolates of O. h. quadrasi based on a 342-bp fragment of the 16S ribosomal RNA gene. O. h. quadrasi isolates were collected from nine provinces known to have S. japonicum in the Philippines, namely Cagayan Valley, Bohol, Negros Occidental, Leyte, Davao, Davao del Sur, Mindoro Oriental, Northern Samar, and Sorsogon. O. h. hupensis and O. h. nosophora isolates were also collected from China and Japan, respectively. The 16S ribosomal RNA gene of each specimen was amplified and sequenced. Phylogenetic and network analyses based on the 221 16S rRNA gene sequences revealed that O. h. quadrasi clustered as a distinct clade from the two other subspecies. Of the four identified haplotypes for O. h. quadrasi , two haplotypes were from Negros Oriental (Ohq2 and Ohq3), and one haplotype was from Bohol (Ohq4). The isolates from the remaining seven provinces shared a common haplotype (Ohq1). The current study was able to show the relationship among O. hupensis subspecies and demonstrate the limited ability of mitochondrial 16S ribosomal molecular marker in differentiating O. h. quadrasi geographic strains in the Philippines. Keywords: O ncomelania hupensis quadrasi, Schistosoma japonicum, Schistosomiasis japonica, Snail Intermediate Host, Haplotype, 16S Ribosomal RNA Gene